An allergic subtype of acquired idiopathic generalized anhidrosis resistant to steroid pulse therapy – a retrospective, single-center, cohort study - Maiko Fujita; Tadatsune Iida; Chie Uchida; Minako Inazawa; Hana Takeshita; Tomoko Fujimoto; Takeshi Namiki; Hiroo Yokozeki; Naoko Okiyama (Journal of Cutaneous Immunology and Allergy)
Steroid pulse therapy is considered effective in the treatment of acquired idiopathic generalized anhidrosis (AIGA). However, nearly half of patients with AIGA do not respond to treatment, or relapse, suggesting the need to stratify patients on the basis of biomarkers to optimize the treatment plan. Although several factors associated with response to treatment, such as the duration since disease onset and serum carcinoembryonic antigen (CEA) levels, have been reported, the relationships between these factors and their effect on the relapse rate have not been evaluated. This retrospective cohort study of 210 patients showed a poor prognosis in patients with high serum total immunoglobulin E (IgE) levels because of a high relapse rate. Serum total IgE levels tended to be inversely related to serum CEA levels, but a multivariate analysis showed that high serum total IgE levels were an independent risk factor for relapse. However, low serum CEA levels were an independent risk factor for non-response to steroid pulse therapy, even after adjustment for factors such as the duration since disease onset, which showed an inverse trend with serum CEA levels. These results suggest that, in addition to the typical subtype of AIGA with high serum CEA levels in the active phase of the disease, there may be an allergic type of the disease with high serum total IgE levels and a poor prognosis with steroids. Therefore, stratifying patients by measuring serum total IgE and CEA levels may aid in predicting the effect of steroid pulse therapy.